Diagnoses of insect diseases: Microbial infections in insects diagnosed as part of the research in developing new ways of controlling crop pests - E Steinhaus (California Agriculture, 1950)
The first successful experiments in microbial control of a California crop pest had their beginning in the diagnostic part of the laboratory of insect pathology in the Division of Biological Control in Berkeley.